Hybrid Color Filters for Multispectral Imaging. Issue 11 (9th September 2020) - He, Xin; Liu, Yajing; Beckett, Paul; Uddin, Md Hemayet; Nirmalathas, Ampalavanapillai; Unnithan, Ranjith Rajasekharan
Abstract: Multispectral cameras capture images in multiple wavelengths in narrow spectral bands. They offer advanced sensing well beyond normal cameras and many single‐sensor‐based multispectral cameras are commercialized aimed at a broad range of applications, such as agroforestry research, medical analysis, and so on. However, the existing single‐sensor‐based multispectral cameras require accurate alignment to overlay each filter on image sensor pixels, which makes their fabrication very complex, especially when the number of bands is large. This paper demonstrates a new filter technology using a hybrid combination of single plasmonic layer and dielectric layers by computational simulations. A filter mosaic of various bands with narrow spectral width can be achieved with single run manufacturing processes (i.e., exposure, development, deposition, and other minor steps) regardless of the number of bands. Abstract : Multispectral imaging camera has the ability to collect information well beyond human eyes or normal color cameras. But the multispectral imaging is limited by conventional optical filter mosaic technology. Here, a hybrid optical filter technology is presented by combining a single plasmonic layer and dielectric layers using computational simulations.